Lunturnya Antusiasme Karawitan di Tanah Nusantara - Qibtiyah, Mariyatul (LoroNG: Media Pengkajian Sosial Budaya, 2012)
Java community prior to the influence of Hinduism has come to know ten of expertise, such as puppets and gamelan (which became one of the musical arts/Karawitan). At present anywhere in the world are found groups of Javanese gamelan and gamelan music. Some of which can be exemplified here is a group Mager Sari in Osaka-Japan, Sumunar in the United States, and Hanuman in Finland. Even when this art Javanese musicians not only belong to the Javanese or Indonesian only, but already belong to the international world. When in fact, the art of Javanese gamelan music contains the values of historical and philosophical for the Indonesian nation. This chips of Karawitan nusantara, let’s enthusiasm again to reproduction and repetitions ours culture. Masyarakat Jawa sebelum adanya pengaruh Hindu telah mengenal sepuluh keahlian, seperti wayang dan gamelan (yang menjadi salah satu seni musik/karawitan). Saat ini banyak ditemukan kelompok gamelan Jawa dan musik gamelan. Beberapa yang dapat dicontohkan di sini adalah kelompok Mager Sari di Osaka-Jepang, Sumunar di Amerika Serikat, dan Hanuman di Finlandia. Bahkan saat ini seni karawitan Jawa bukan hanya milik orang Jawa atau Indonesia saja, tapi sudah milik dunia internasional. Padahal sebenarnya, seni musik gamelan Jawa mengandung nilai-nilai historis dan filosofis bagi bangsa Indonesia asli. Inilah nasib karawitan nusantara, mari kita berantusiasme kembali untuk mereproduksi dan merepetisikan kembali budaya kita.